Apreciación de los empleadores de las organizaciones del sector comercial del departamento del Quindío sobre la calidad de la formación y el desempeño de los egresados del programa de Contaduría Pública de la Universidad del Quindío. (2014)
The University of Quindío in its Public Accounting Program states as the vision the university background with high quality standards as the main reason to carry out the requirements demanded by Consejo Nacional de Acreditación (CNA, 1998) to certify the high quality academic programs in higher education; this process consists of some quality criteria which addresses to different stages of the evaluation which are self-evaluation, external evaluation and final evaluation. The first one is done by the institution itself to measure the current quality of the program; the second one is done by the academic peers from the CNA to verify the self-evaluation results done by the institution, and the third one is the approving or disapproving concept which arises from the self-evaluation and external evaluation results.